DEVELOPMENT OF SUBJECTNESS IN THE AXIOSPHERE OF UNIVERSITY YOUTH SUBCULTURE - Aida V. Kiryakova; Lyudmila V. Mosienko; Tatyana A. Olkhovaya (Высшее образование в России)
The authors consider an axiosphere of university youth subculture as a factor of university student’s subjectness formation, which determines his successful educational and professional activities. Axiosphere is formed by constant and variable values of university youth subculture and includes academic, professional, civil, virtual, hedonistic, social, personal, valeological, and corporate values. Personal development of a student as a subject is a continual and phasic process including adaptation, orientation and personalization stages. Some pedagogical conditions ensure successfulness of this process.